2012
DOI: 10.5755/j01.em.17.4.2991
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Problems of Projects Implemented by Companies and Co-Financed by the European Union Funds in Latvia

Abstract: The aim of the research is to study the correlations of the risk degree of the projects co-financed by the European Union (EU) funds and implemented by companies in Latvia with the amount of non-obtained project co-financing during their implementation. Findings: The research shows that in all phases of the project cycle, starting with planning and finishing with implementation a great role in achieving of project aims is paid by a qualitative risk management process that allows identify early and prevent diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…The current Ghana banking sector is faced with serious major challenges such as the employee's habit of stealing and mismanagement of banks vital documents to take undue advantage over the system control [8]. Recent empirical research relating to internal controls by Munene [9], revealed that some of the challenges experienced with regard to internal controls include; liquidity problems, inaccurate financial reports, misallocation and financial resources accountability issues, circumventing of institutional procedures and fraud.…”
Section: Introductionmentioning
confidence: 99%
“…The current Ghana banking sector is faced with serious major challenges such as the employee's habit of stealing and mismanagement of banks vital documents to take undue advantage over the system control [8]. Recent empirical research relating to internal controls by Munene [9], revealed that some of the challenges experienced with regard to internal controls include; liquidity problems, inaccurate financial reports, misallocation and financial resources accountability issues, circumventing of institutional procedures and fraud.…”
Section: Introductionmentioning
confidence: 99%